Damage and recovery of forest structure and composition after two subsequent hurricanes in the Yucatan Peninsula - Martha Bonilla-Moheno (Caribbean Journal of Science, 2010)
Hurricanes are important disturbances shaping tropical forest structure. In the last 35 years the frequency and intensity of these events have changed, and it is predicted that intense hurricanes will become even more frequent with continued ocean surface warming. In 2005, the northeastern region of the Yucatan peninsula was hit by two subsequent category-5 hurricanes (3 months apart), Emily and Wilma. I conducted vegetation surveys to evaluate forest structure and composition soon after each disturbance and after one year, determining number of species, number of stems, basal area, and type of impact presented (defoliated, snapped, or uprooted), for all stems ≥ 5 cm DBH in two different forest stand ages (8-15 yr and > 30 yr). Number of species and basal area varied by forest stand age and survey; stem density decreased after the hurricanes. The highest percentage of damaged individuals was after the second hurricane (60%), but one year later this percentage was greatly reduced (13%).